Daily cycle of melatonin in different tissues of dybowski's frog (Rana dybowskii). Issue 9 (2nd September 2022) - Hu, Nan; Wang, Junnan; Zhao, Yingying; Wei, Hua; Li, Xiang; Li, Yingdong
ABSTRACT: This study is the first to analyse the daily cycle of melatonin in Dybowski's frogs ( Rana dybowskii ), a species with economic importance in north-eastern China. The concentrations of melatonin in the serum, whole brain, and liver, skin, and retinal tissue samples collected from Dybowski's frogs were measured using high-performance liquid chromatography every 4 h over a 24 h cycle. A significant melatonin peak ( P < 0.05) was observed at 00:00 in the serum samples (203.25 ± 5.06 ng/L). This peak was synchronised with peak melatonin concentrations in the retinal (1513.25 ± 3.15 ng/L), liver (49.34 ± 3.67 ng/L), and whole brain (426.85 ± 6.85 ng/L) tissue samples, although melatonin concentrations in skin tissue samples peaked at 12:00 (270.02 ± 4.60 ng/L). Therefore, the time of day should be considered when examining the physiological status of this frog, given the potential effects of fluctuating daily melatonin concentrations on physiological variables.